2010
DOI: 10.1007/s11104-010-0527-7
|View full text |Cite
|
Sign up to set email alerts
|

Metal uptake by xerothermic plants introduced into Zn-Pb industrial wastes

Abstract: The dusty surfaces of post-flotation wastes contain high concentrations of toxic compounds and spread widely if appropriate vegetation is not introduced. It has been previously established that effective restoration of such waste areas are best met by xerothermic, mycorrhiza-assisted plants (Turnau et al. Plant and Soil 305:267-280, 2008). The aim of the current study was to improve phytostabilisation practices by gaining insight into the elements uptake in plants after their change of habitat. Total Reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
2
17
2
Order By: Relevance
“…As shown in the present study, plants from control treatment contained more Ca when growing in the waste substrates. These results are in close agreement with those reported by Turnau et al [30]. Silicon may affect the bioavailability of Ca for plants.…”
Section: Plant Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in the present study, plants from control treatment contained more Ca when growing in the waste substrates. These results are in close agreement with those reported by Turnau et al [30]. Silicon may affect the bioavailability of Ca for plants.…”
Section: Plant Analysissupporting
confidence: 93%
“…However, species used for the 'grass mix' combination belong to xerothermic plants, which are commonly lownutrient requirements. Turnau et al [30] found that plants growing on the industrial waste substrates generally had greater concentrations of heavy metals (Zn, As, Pb, and Fe) and lower concentrations of K than plants from ) of 'herbs mix' production in different green roof substrates, and element concentrations (% d.m.) in plant biomass.…”
Section: Plant Analysismentioning
confidence: 99%
“…Research findings suggest them as ideal candidates for phytoremediation of both saline and non-saline, heavy metal polluted soils, such as Atriplex halimus (Mesnoua et al 2016), Mesembryanthemum crystallinum (Lutts and Lefèvre 2015), Atriplex canescens, Suaeda vera (Ayyappan and Ravindran, 2014), Calendula officinalis L. (Hristozkova et al 2016), Marrubium vulgare (Belabed et al 2014), Limbarda crithmoides subsp. longifolia and Dittrichia viscosa (Turnau et al 2010). The floristic survey showed that DM site has more diversified plant species than LT (34 plant species in DM, and 28 in LT), while the flora has not been affected, despite the high Pb, Cr and Cd concentrations in the soil, due to the presence of different native heavy metal accumulator plants.…”
Section: Discussionmentioning
confidence: 97%
“…Verbascum plants are widespread from the temperate to the subtropical zones and have modest soil requirements (Zielińska-Pisklak et al 2013). They occur spontaneously and grow well at the slope of the tailings near Kraków (Poland), where growing conditions are extremely difficult (Turnau et al 2010;Turnau et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Mulleins are also being utilized by the pharmaceutical industry. Verbascum species show potential for bioremediation of polluted soils accumulating toxic metals such as As, Pb, Zn (Turnau et al 2010), Ba (Kowalska et al 2012) Mo, Cu and Ag (Sagiroglu et al 2006). …”
Section: Introductionmentioning
confidence: 99%